Forests, foragers and empires : Socionatural histories of Southern India - Morrison, Kathleen D. (Delhi : Primus Books, 2024)
Forests, Foragers, and Empires: Socionatural Histories of Southern India explores the complex histories of south Indian forests and foragers, focusing on historical recognitions and misrecognitions emerging from prior assumptions about human and non-human history, and about presumed fundamental characteristics of 'nature' and 'culture'. Many of these essays focus on the hunting and gathering peoples of southern India, especially as they have articulated with others throughout the Holocene. Other essays consider the larger-scale landscape histories within which these are situated, from the forests themselves to local and long-standing networks of production, trade, and power. These histories include multiple forms of agency-kings, hunters, merchants, farmers, sailors, city-dwellers, and of course plants, animals, and the forests themselves. This collection of essays aims to reinsert both forests and foragers into mainstream South Asian history, including the history of European colonial expansion and conquest, as well as those of other imperial polities.
Keywords: Forests and forestry -- History -- India; South -- Asia; Human ecology -- History -- India; Hunting and gathering societies -- History -- India; South -- Asia